Credit risk management and the performance of Nigerian deposit money banks - P. O. Okey-Nwala, P. O. Okey-Nwala; Ndubuisi, J. I. Kenn-; Wachukwu, P. I. (BOHR International Journal of Finance and Market Research, 2023)
We have used a multiple regression model to identify the impacts of the variables of credit risk management on the Nigerian deposit money banks’ performance from 2000 to 2020. The estimation was completed using the ordinary least squares method with E-Views 12. The data was sourced from the Nigerian Stock Exchange for information and the Statistical Bulletin of the Central Bank of Nigeria. The outcome determined that return on equity (ROE) is negatively correlated with the nonperforming loan/loan and advances ratio. Last but not least, the ROE measurements of the deposit money banks in Nigeria show a substantial correlation between the ratios of advances and loans to nonperforming loans, loan loss provision to loans and advances, and capital adequacy. These ratios are positively correlated with each other and negatively correlated with the capital adequacy ratio. We advise effective surveillance of pre- and post-deposit financial institution loans for the early detection of problematic debts that won’t be repaid according to schedule and for the thorough analysis of prospective projects as indicated in the financial statement given by the intended client (cash budget, income statement). Accurate identification of realistic projects and repayment terms based on the customer’s past performance will be achieved.